IoT-based heartbeats monitoring system - Mohd Tamron, Mohamad Asyraf Noorza; Attarbashi, Zainab; Abuzaraida, Mustafa Ali; Atitallah, Nesrine; Iftikhar, Saman; Handayani, Dini Oktarina Dwi; Basri, Atikah Balqis (IEEE, 2023)
The advent of the Internet of Things (IoT) has opened up a realm of possibilities in developing globally accessible systems and devices. With the current state of internet speeds, these systems offer real-time control, making them more powerful than ever. Simultaneously, the healthcare sector has been witnessing notable advancements, but it also grapples with an increasing number of health issues, with heart problems standing out as a prominent concern in many countries. These problems manifest in various symptoms, some of which can lead to more serious conditions, such as irregular heartbeats. In response to these challenges and leveraging cutting-edge technology, researchers have embarked on endeavors to enhance healthcare devices and render them more readily available to medical professionals. This paper explores the merging of IoT technology with healthcare, specifically focusing on the development of a system designed to monitor and record a patient's heartbeat. This is achieved through the deployment of a Heartbeat/SpO2 Sensor, and the data is seamlessly transmitted to a mobile application accessible remotely. The outcomes of this study demonstrate that the heartbeat data captured by Arduino is effectively transmitted to the cloud, meeting the system's predefined objectives. This represents a significant stride in harnessing IoT's potential to enhance healthcare practices and patient monitoring.